Generalized bullous fixed drug eruption due to fluconazole: A report of two cases - Anuva Bansal (Indian Journal of Drugs in Dermatology, 2021)
Fixed drug eruption (FDE) is characterized by the development of well-demarcated erythematous to violaceous plaques, within minutes to hours of the intake of an offending drug. It is known as “fixed” because subsequent exposure to the implicated drug leads to the development of lesions at the same sites that were involved at the time of the previous drug exposure. Fluconazole, a widely used antifungal agent, has a good safety profile, and limited data exist on the development of bullous FDE due to fluconazole. Herein, we report a series of two cases presenting with a generalized bullous FDE (GBFDE), following the consumption of fluconazole. A temporal correlation, typical morphological features, symptoms, and a past history of FDE due to fluconazole were essential clues to the diagnosis. Furthermore, we utilized the Naranjo adverse drug reaction probability scale for causality assessment. Discontinuation of the drug was followed by the resolution of lesions in 7–10 days. GBFDE is an uncommon entity and requires immediate diagnosis as well as prompt discontinuation of the offending agent to minimize the complications.